Hesperidin - loaded PVA/alginate hydrogel: targeting NFκB/iNOS/COX-2/TNF-α inflammatory signaling pathway - Kodous, Ahmad S.; Abdel-Maksoud, Mostafa A.; El-Tayeb, Mohamed A.; Al-Sherif, Diana A.; Mohamed, Suzan Shawky Abuelkasem; Ghobashy, Mohamed Mohamady; Emad, Ayat M.; Abd El‐Halim, Shady M.; Hagras, Soheir A. A.; Mani, Samson; Rao, Arunagiri Kuha Deva Magendhra; Hussein, Ahmed M.; et al. (Frontiers in Immunology, 2024)
Skin injuries are a prevalent form of trauma, requiring effective therapeutic strategies for wound healing. Hesperidin, a bioflavonoid found in citrus fruits, possesses various pharmacological properties, including antimicrobial, antioxidant, anti-inflammatory, anticoagulant, and analgesic effects. This study aimed to formulate a biodegradable hydrogel to address skin conditions, focusing on wound healing. The research presents a methodology for creating a membrane composed of Polyvinyl alcohol - Sodium Alginate (PVA/A) blend, incorporating the anti-inflammatory agent Hesperidin (H) to enhance wound healing. A uniform layer of PVA/A solution was cast and crosslinked using gamma irradiation at 30 kGy to improve hydrogel characteristics. The membrane was then immersed in a Hesperidin solution to enable controlled drug delivery. The resulting system aims to deliver Hesperidin efficiently for wound healing. The PVA/AH hydrogel was evaluated for cytotoxicity, antioxidant activity, anti-inflammatory effects, and membrane stability. Additionally, its impact on oxidative stress and inflammatory markers was assessed on BJ-1 human skin cells. The radical scavenging activity of PVA/AH was 87%, while hemolysis inhibition was 81.97% and 84.34%, respectively, compared to diclofenac (Dic.) and aspirin (Asp.) at 250 μg/ml. Gene expression analysis showed upregulation of antioxidant and anti-inflammatory genes and downregulation of TNFα, NFκB, iNOS, and COX2 by PVA/AH hydrogel compared to LPS-stimulated BJ-1 cells. The antioxidant and anti-inflammatory properties of Hesperidin contribute to its benefits in wound healing. Incorporating Hesperidin into hydrogels presents a promising approach for wound treatment, leveraging the collaborative qualities of PVA/AH and gamma irradiation to establish a drug delivery platform.